Combination therapy with liposomal neuroprotectants and tissue plasminogen activator for treatment of ischemic stroke. Issue 5 (12th January 2017) - Fukuta, Tatsuya; Asai, Tomohiro; Yanagida, Yosuke; Namba, Mio; Koide, Hiroyuki; Shimizu, Kosuke; Oku, Naoto
ABSTRACT: For ischemic stroke treatment, extension of the therapeutic time window (TTW) of thrombolytic therapy with tissue plasminogen activator (tPA) and amelioration of secondary ischemia/reperfusion (I/R) injury are most desirable. Our previous studies have indicated that liposomal delivery of neuroprotectants into an ischemic region is effective for stroke treatment. In the present study, for solving the above problems in the clinical setting, the usefulness of combination therapy with tPA and liposomal fasudil (fasudil‐Lip) was investigated in ischemic stroke model rats with photochemically induced thrombosis, with clots that were dissolved by tPA. Treatment with tPA 3 h after occlusion markedly increased blood–brain barrier permeability and activated matrix metalloproteinase (MMP)‐2 and −9, which are involved in cerebral hemorrhage. However, an intravenous administration of fasudil‐Lip before tPA markedly suppressed the increase in permeability and the MMP activation stemming from tPA. The combination treatment showed significantly larger neuroprotective effects, even in the case of delayed tPA administration compared with each treatment alone or the tPA/fasudil‐treated group. These findings suggest that treatment with fasudil‐Lip before tPA could decrease the risk of tPA‐derived cerebral hemorrhage and extend the TTW of tPA and that the combination therapy could be a useful therapeutic option for ischemic stroke.—Fukuta, T., Asai, T., Yanagida, Y., Namba, M., Koide, H., Shimizu, K., Oku, N. Combination therapy with liposomal neuroprotectants and tissue plasminogen activator for treatment of ischemic stroke. FASEB J. 31, 1879–1890 (2017). www.fasebj.org